Job Satisfaction and Work Motivation in Enhancing Generation Z’s Organizational Commitment - Putri Rakhmatia Nabahani; Setyo Riyanto (Journal of Social Science, 2020)
Generation Z is a generation with unique characteristics that makes them differ from their predecessor. With Generation Z entering the workplace, there are currently three generations (Gen X, Gen Y, and Gen Z) that must work together and coordinate within the company. However, Generation Z is known to be a “job hopper” generation. They like to switch between jobs for a certain reason. This behavior is surely associated with the concept of organizational commitment. Furthermore, both variables (motivation and satisfaction in work) presumed to have a great impact on organizational commitment. Therefore, the aim of this study is to observe on how to enhance Generation Z’s organizational commitment through job satisfaction and work motivation. This observation is to explain on what Generation Z expects and values the most in the workplace and how employers can meet those expectations. Research method used is desktop-based research which consists of secondary data collected from different research papers, journals, articles, and books.